Method for improving gas extraction rate by extracting geothermic energy - ZHU CHUANJIE; LIN BAIQUAN; YANG KAI; LU XIMIAO; GAO ZISHAN (2018)
The invention discloses a method for improving a gas extraction rate by extracting geothermic energy. The method comprises the following steps: firstly, constructing and drilling in a heat source rocklayer and burying a heat collection heat pipe; evaporating and condensing a working medium and rapidly transferring heat to a heat collection water tank through the heat collection heat pipe; carrying out heat exchange on the heat collection water tank and a heat source water tank through a heat exchanger, so as to heat water in the heat source water tank; distributing a heating heat pipe in a gas extraction drilled hole and heating an extraction coal layer by the heat source water tank through the heating heat pipe; continuously transferring the heat into the extraction coal layer along continuous phase change of an evaporation section and a condensation section of the working medium in the heating heat pipe. The method disclosed by the invention is high in heat transferring efficiency;an extra direct heat sourc